Influencia de la violencia intrafamiliar en la conducta sexual de una adolescente de 15 años de edad - Viteri Galeas, Ariana Tatiana (2019)
Intra-family violence is characterized by exercising control over a person or situation, usually from a family member of high hierarchical levels, with progressive repercussions in which there may be beatings, and sexual abuse. The consequences on the victim of domestic violence in the emotional area range from low self-esteem, to thoughts of self-harm, anger; As for the social cognition area, there are problems with both sexes, anxiety in intimidation, mistrust, abandonment of home, fear of maintaining sexual behavior or promiscuity; in the behavioral area are self-harm, suicidal thoughts and attempts, alcohol or drug use, and poor school performance. The types of research applied are: descriptive research, explanatory research, and medical history, resulting in the test called Person in the rain, proposing solutions such as individual and family therapy to develop correct social techniques